2012
DOI: 10.1111/j.1744-7348.2012.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature‐induced reductions in cropping in everbearing strawberries (Fragaria × ananassa) are associated with reduced pollen performance

Abstract: Heat‐induced short‐term reductions in cropping (often referred to as ‘thermodormancy’ by UK strawberry growers) occur frequently in extended‐season everbearing strawberry production in the UK. A 2‐year study evaluated the effects of high temperatures on the performance of pollen in two everbearing strawberry cultivars (cvs ‘Everest’ and ‘Diamante’). Pollen from both cultivars lost its ability to germinate following exposure to a period of high temperature (30/20°C day/night). However, after termination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…They also reported that 30°C and 75-85% humidity lowered pollen germination for all cultivars that were evaluated. Karapatzak et al (2012) found lower germination levels for two strawberry cultivars that were exposed to high temperatures (30/20°C day/night), compared to plants exposed to lower temperatures (22°C/15°C, 26°C/11°C). In another study, the lowest in vitro pollen germination levels were determined at 7°C for Elvira, Selva, and Chandler, and 15°C for Cavendish, Allstar, and Elsanta (Koyuncu, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…They also reported that 30°C and 75-85% humidity lowered pollen germination for all cultivars that were evaluated. Karapatzak et al (2012) found lower germination levels for two strawberry cultivars that were exposed to high temperatures (30/20°C day/night), compared to plants exposed to lower temperatures (22°C/15°C, 26°C/11°C). In another study, the lowest in vitro pollen germination levels were determined at 7°C for Elvira, Selva, and Chandler, and 15°C for Cavendish, Allstar, and Elsanta (Koyuncu, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…Temperature directly influences the length of the growing season, and therefore fluctuations in the climate would result in irregular flowering patterns [35]. When tunnel temperatures increase unexpectedly, high temperatures may affect flower and fruit quality as well as quantity [13,[36][37][38][39]. Although the effect of high temperature on the development of reproductive and vegetative structures in EB cultivars have been previously reported [13,38,40,41], in most of these studies the plants were moved after treatment in control climate rooms optimal for growth.…”
Section: Introductionmentioning
confidence: 99%
“…They referred to this phenomena as thermodormancy. Karapatzak et al [13] did not find such a strong inhibition of flowering at high temperatures in another study of 'Everest' and 'Diamante', but they did find pollen germination to be greatly inhibited at high temperatures (30/20 • C). Bradford et al [5] found the threshold temperature for floral inhibition to be 23 • C in SD 'Honeoye' and 26 • C in DN 'Tribute' and a wild SD selection of F. virginiana.…”
Section: Introductionmentioning
confidence: 92%